The Implementation of Character Education to Improve Social Skills of Elementary School Students - Sofyan, Ahsan; Saputra, Ady (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Education is one of the main keys to building and shaping citizens' character quality. One of the skills in education is social skills. This research aims to determine the implementation of character education in the formation of social skills in elementary schools. The research method used is the descriptive qualitative research method. The subjects in this study were teachers and elementary school students. Instrument content validation was carried out by consulting the validator team. Methods of data collection using interviews, questionnaires, and documentation. The results of this study show that there is an influence between character education by carrying out routine religious activities, instilling a nationalist spirit, carrying out tasks independently, cooperation, and helping others in terms of goodness, which is then integrated into everyday life to foster social attitudes in the form of honesty, discipline, responsibility, polite, caring and confident so, the application of character education has a good impact on social attitudes in students.